(untitled) (IAHS Medical Journal, 2024)
Background: Consent means free, valid, voluntary agreement, approval, or permission for compliance with some act. Many doctors get involved in medical negligence during professional practice, probably due to a lack of accurate documentation or consent. Para-clinical medical students are at the initial stages of learning about consent. The present study was conducted to assess the knowledge about consent in medical practice among them. Materials and methods: A cross-sectional survey was conducted from September 2022 to December 2022 on 200 para-clinical medical students of Chattagram Maa-O-Shishu Hospital Medical College. A self-administered structured questionnaire was used and data were analyzed by SPSS-V.20. Results: Among the students, the majority were female (63.5%) and Muslim (83.5%). The age range of the participants was 20–24 years. It was found that 97% of the students had knowledge about the various types of consent in rational medical practice. 73.5% were satisfied with their knowledge about consent in medical practice. 91% believed that written consent was the best type of consent in medical practice. Major participants (89%) believed that only a person over 18 years of age with a sound mind could provide valid consent for general physical examinations and procedures. The majority (88%) felt the need of regular CME on consent. Statistically no association was found with knowledge about consent to gender and phase distribution (p>0.05). Conclusion: This study indicated that the most of the participants were aware of consent and had sufficient knowledge on it. Arranging seminars, workshops and CME would reduce the gap and help in building a constructive attitude toward the necessity of updating knowledge about consent in medical practice. IAHS Medical Journal Vol 6(1), June 2023; 25-29